TESTICULAR CYTOTOXITY OF INTRAVENOUS CIS-PLATIN IN COMBINATION WITH FOSFOMYCIN IN RATS - MANABE, FUMIO; YOSHII, SHIN-ICHI; KOISO, KENKICHI; ISHIKAWA, HIROMICHI; TOMOMASA, HIROSHI; OOTANI, MIKINOBU (CHEMOTHERAPY, 1990)
In an animal model we assessed testicular cytotoxity of intravenous cis-platin (CDDP), which was combined with fosfomysin (FOM) in order to reduce renal danage. We used 10-week-old male postpubertal Fisher 334 rats, and administered CDDP (6mg/kg, 5mg/kg ×2 days) alone or in combination with 400mg/kg/day of FOM. Four and eight weeks after the last injection, the weight of testes and kidneys and the serum levels of TP, BUN, CRE and NAG were measured. Four weeks after the last injection, the weight of testes in group 8 (CDDP 5mg/kg ×2 days, FOM 400mg/kg/day) had significantly decreased and histologically a few seminiferous tubules without spermatids were found. All rats in groups 12 and 13 (CDDP 5 mg/kg ×2 days) died within one week. In group 9 (CDDP 5 mg/kg ×2 days) eight weeks after the last injection, the damaged testes recovered histlogically, and their weight was not significantly different from that of controls. We considered that the testicular cytotoxity of cis-platin was slight and reversible, and that FOM was effective in increasing the tolerable dose of cis-platin.